2023
DOI: 10.3389/fmicb.2023.1252973
|View full text |Cite
|
Sign up to set email alerts
|

Bio-protection in oenology by Metschnikowia pulcherrima: from field results to scientific inquiry

Maëlys Puyo,
Scott Simonin,
Benoit Bach
et al.

Abstract: Finding alternatives to the use of chemical inputs to preserve the sanitary and organoleptic quality of food and beverages is essential to meet public health requirements and consumer preferences. In oenology, numerous manufacturers already offer a diverse range of bio-protection yeasts to protect must against microbiological alterations and therefore limit or eliminate sulphites during winemaking. Bio-protection involves selecting non-Saccharomyces yeasts belonging to different genera and species to induce ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 127 publications
0
8
0
Order By: Relevance
“…Previous research has also indicated that autochthonous yeasts are predominantly sensitive or neutral ( Comitini et al, 2011 ; Domizio et al, 2011 ; de Ullivarri et al, 2014 ; Velázquez et al, 2016 ). The lack of killer properties in the isolated yeasts of the current survey, justifies the strain biodiversity among wine samples at the end of AF ( Puyo et al, 2023 ). Furthermore, a brief overview of the literature over the past few decades supports that the most preferable strains should be characterized by non or low production of H 2 S in order to be used as starter cultures ( Caridi et al, 2002 ; Settanni et al, 2012 ; Aponte and Blaiotta, 2016 ).…”
Section: Discussionmentioning
confidence: 85%
“…Previous research has also indicated that autochthonous yeasts are predominantly sensitive or neutral ( Comitini et al, 2011 ; Domizio et al, 2011 ; de Ullivarri et al, 2014 ; Velázquez et al, 2016 ). The lack of killer properties in the isolated yeasts of the current survey, justifies the strain biodiversity among wine samples at the end of AF ( Puyo et al, 2023 ). Furthermore, a brief overview of the literature over the past few decades supports that the most preferable strains should be characterized by non or low production of H 2 S in order to be used as starter cultures ( Caridi et al, 2002 ; Settanni et al, 2012 ; Aponte and Blaiotta, 2016 ).…”
Section: Discussionmentioning
confidence: 85%
“…Interestingly, after inoculation with M. pulcherrima UASWS2926 VBI-A02, the relative abundance of these microorganisms was reduced, especially the most "risky" from a spoilage perspective (in particular, they increase volatile acidity), such as Hanseniaspora. This bioprotective effect exerted by M. pulcherrima is currently being studied extensively from the perspective of a continuous reduction in chemical inputs, such as sulfites [40]. However, it is important to point out that bioprotection is usually carried out in must clarification/maceration steps at low temperatures, conditions that favor biocontrol by M. pulcherrima [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…While there has been extensive research on the biological control of postharvest fruits and vegetables using antagonistic yeasts, the focus of research on the biological protection of fruit juice has mainly been on grape juice [ 185 ]. However, there has been some recent research on the use of antagonistic yeasts for the biological protection of other types of fruit juice.…”
Section: Biopreservation Of Yeasts In Processed Foodsmentioning
confidence: 99%